Metal cluster catalyst, its preparation method and application

CN122955494APending Publication Date: 2026-10-23CHINA PETROLEUM & CHEMICAL CORP +1
View PDF 0 Cites 0 Cited by

Patent Information

Application Number
CN202510509836.2
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2025-04-22
Publication Date
2026-10-23

AI Technical Summary

Technical Problem

一旦将金属载量提高,金属原子即会发生团聚、颗粒长大,导致催化剂的活性明显下降

Benefits of technology

[0022]通过上述技术方案,本公开的催化剂包括载体和负载在载体上的活性金属;载体为硫改性的碳载体,活性金属包括Ru、Pd和Ir中的一种或多种;其中,在该催化剂的XRD谱图中,在2θ为39.5~43.0°处特征峰的单位质量金属归一化峰强度与半峰全宽之比不大于1.5,且在2θ为67.0~69.0°处特征峰的单位质量金属归一化峰强度与半峰全宽之比不大于0.2。本公开的催化剂在高载量下,金属以原子团簇的形式存在,具有较好的分散性,相比于商业催化剂具有较高的活性和稳定性。

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN122955494A_ABST
    Figure CN122955494A_ABST
Patent Text Reader

Abstract

The present disclosure relates to a metal cluster catalyst, a preparation method and application thereof, the catalyst comprising a carrier and an active metal supported on the carrier; the carrier is a sulfur-modified carbon carrier, and the active metal comprises one or more of Ru, Pd and Ir; wherein, in the XRD spectrum of the catalyst, the ratio of the unit mass metal normalized peak intensity to the full width at half maximum of the characteristic peak at 2theta of 39~43° of the active metal is not more than 1.5, and the ratio of the unit mass metal normalized peak intensity to the full width at half maximum of the characteristic peak at 2theta of 67~69° is not more than 0.2. The catalyst of the present disclosure has good dispersibility with the metal in the form of atomic clusters at high load, and has higher activity and stability compared with commercial catalysts.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] This disclosure relates to the field of electrochemical technology, and more specifically, to a metal cluster catalyst, its preparation method, and its application. Background Technology

[0002] Most chemical processes require catalysts, among which noble metal catalysts play a crucial role due to their extremely high activity and stability, such as in hydrogenation / dehydrogenation reactions and water electrolysis for hydrogen production in modern chemical and new energy processes. To reduce the amount of noble metals used, single-atom and small-particle-size atomic cluster catalysts have become a research hotspot in recent years. However, these catalysts have very low metal loadings; although the activity per unit mass of metal is high, the overall activity of the catalyst is usually low. Increasing the metal loading leads to metal agglomeration and particle growth, resulting in a significant decrease in catalyst activity. Summary of the Invention

[0003] The purpose of this disclosure is to provide a metal cluster catalyst, its preparation method and application. Under high loading, the metal exists in the form of atomic clusters, exhibiting good dispersibility and higher activity and stability compared to commercial catalysts.

[0004] To achieve the above objectives, this disclosure provides a metal cluster catalyst, the catalyst comprising a support and an active metal supported on the support; the support is a sulfur-modified carbon support, and the active metal comprises one or more of Ru, Pd, and Ir; In the XRD spectrum of the catalyst, the ratio of the normalized peak intensity per unit mass to the full width at half maximum (FWHM) of the characteristic peak of the active metal at 2θ of 39.5–43.0° is not greater than 1.5, and the ratio of the normalized peak intensity per unit mass to the full WHM of the characteristic peak at 2θ of 67.0–69.0° is not greater than 0.2.

[0005] Optionally, in the STEM image of the catalyst, the proportion of metal particles with regular lattice stripes is less than 60%, preferably 10-50%.

[0006] Optionally, based on the total mass of the catalyst, the mass fraction of the active metal is 1-70%, preferably 5-50%.

[0007] Optionally, the active metal is formed as an atomic cluster, the average particle size of which is 1-5 nm.

[0008] Optionally, the active metal is Ru, and the mass fraction of Ru is 1-70% based on the total mass of the catalyst. In the XPS spectrum of the catalyst, the 3p 3 / 2 characteristic peak of 0-valent Ru is located at 461.0~463.0 eV; In the XRD pattern of the catalyst, a Ru characteristic peak is present or absent at 2θ of 39.5~43.0°.

[0009] Optionally, the active metal is Ir, and the mass fraction of Ir is 1-70% based on the total mass of the catalyst. In the XPS spectrum of the catalyst, the characteristic peak position of 4f 7 / 2 for 0-valent Ir is 60.8~61.4 eV; In the XRD pattern of the catalyst, there is an Ir characteristic peak or no Ir characteristic peak at 2θ of 39.5~43.0°.

[0010] Optionally, the active metal is Pd, and the mass fraction of Pd is 1-60%, preferably 5-50%, based on the total mass of the catalyst. In the XPS spectrum of the catalyst, the peak position of the 3d 5 / 2 characteristic peak of 0-valent Pd is 335.2~335.5 eV, and the peak position of the 3d 5 / 2 characteristic peak of divalent Pd is 336.2~336.6 eV; In the XRD pattern of the catalyst, a Pd characteristic peak is present or absent at 2θ of 39.5~43.0°.

[0011] Optionally, in the sulfur-modified carbon support, the total sulfur content is 1-8% by weight, preferably 3-6% by weight. Preferably, the sulfur content on the surface of the sulfur-modified carbon support is 0.1-6% by weight, and more preferably 0.5-3% by weight.

[0012] A second aspect of this disclosure provides a method for preparing a metal cluster catalyst, the method comprising: (1) The metal source and the sulfur-modified carbon support are first impregnated in a solvent, and the precursor is obtained after removing the solvent; (2) The precursor is heat-treated at 230~480°C in an inert atmosphere; The metal source includes one or more of ruthenium, palladium, and iridium.

[0013] Optionally, in step (1), the method for preparing the sulfur-modified carbon support includes: subjecting the carbon support to a second impregnation with a solution containing sulfur; The conditions for the second impregnation include: a temperature of 10~80℃, a time of 1~5h, and a weight ratio of the carbon carrier to sulfur of 2~20:1.

[0014] Optionally, the carbon support is conductive carbon black; the oxygen content of the conductive carbon black is 4% by weight or more; the resistivity of the conductive carbon black is less than 10 Ω·m; and the specific surface area of ​​the conductive carbon black is 200~2000 m². 2 / g.

[0015] Optionally, the ruthenium source is a ruthenium-containing soluble compound, including one or more of ruthenium trichloride and ammonium ruthenate. In step (1), the amount of ruthenium source, calculated as ruthenium, is 0.01~2.4g relative to 1g of the sulfur-modified carbon support, preferably 0.1~1.5g.

[0016] Optionally, the palladium source is a palladium-containing soluble compound, including one or more of palladium chloride, ammonium chloropalladate, and sodium chloropalladate; In step (1), the amount of palladium source, calculated as palladium element, is 0.01~1.5g relative to 1g of the sulfur-modified carbon support, preferably 0.1~1.0g.

[0017] Optionally, the iridium source is an iridium-containing soluble compound, including one or more of chloroiridium acid and iridium trichloride; In step (1), the amount of the iridium source, calculated as iridium, is 0.01 to 2.4 g, preferably 0.1 to 1.5 g, relative to 1 g of the sulfur-modified carbon support.

[0018] Optionally, in step (1), the conditions for the first impregnation include: the impregnation temperature is 10~50℃, preferably 15~40℃, and the impregnation time is more than 10h, preferably 15~24h.

[0019] Optionally, in step (2), the inert atmosphere is one or more of nitrogen and argon; Optionally, the heat treatment conditions include: a temperature of 240~400℃ and a time of 1~4h.

[0020] The third aspect of this disclosure provides a metal cluster catalyst prepared by the method described in the second aspect of this disclosure.

[0021] This fourth aspect of the disclosure provides the application of the metal cluster catalysts described in the first and third aspects of the disclosure in water electrolysis and catalytic addition / dehydrogenation reactions.

[0022] The catalyst disclosed herein comprises a support and an active metal supported on the support. The support is a sulfur-modified carbon support, and the active metal includes one or more of Ru, Pd, and Ir. In the XRD pattern of this catalyst, the ratio of the normalized intensity of the characteristic peak at 2θ of 39.5–43.0° to the full width at half maximum (FWHM) is no greater than 1.5, and the ratio of the normalized intensity of the characteristic peak at 2θ of 67.0–69.0° to the FWHM is no greater than 0.2. Under high loading, the metal in this catalyst exists in the form of atomic clusters, exhibiting good dispersibility and higher activity and stability compared to commercial catalysts.

[0023] Other features and advantages of this disclosure will be described in detail in the following detailed description section. Attached Figure Description

[0024] The accompanying drawings are provided to further illustrate the present disclosure and form part of the specification. They are used together with the following detailed description to explain the present disclosure, but do not constitute a limitation thereof. In the drawings: Figure 1 These are the XRD patterns of Examples 1, 4, and Comparative Examples 1-2.

[0025] Figure 2 These are XPS images of Pd 3d for Examples 1, 4, and Comparative Examples 1-2.

[0026] Figure 3 This is the XRD pattern of Example 2.

[0027] Figure 4 This is the XRD pattern of Example 3.

[0028] Figure 5 This is the Ru 3p XPS diagram of Example 2.

[0029] Figure 6 This is the Ir 4f XPS diagram of Example 3.

[0030] Figure 7 This is a STEM image of Example 1.

[0031] Figure 8 This is a STEM image of Example 2.

[0032] Figure 9 This is a STEM image of Example 3.

[0033] Figure 10 This is a STEM image of Example 4.

[0034] Figure 11 This is the STEM image of Comparative Example 3. Detailed Implementation

[0035] The specific embodiments of this disclosure will be described in detail below with reference to the accompanying drawings. It should be understood that the specific embodiments described herein are for illustration and explanation only and are not intended to limit this disclosure.

[0036] This disclosure provides a metal cluster catalyst, the catalyst comprising a support and an active metal supported on the support; the support is a sulfur-modified carbon support, and the active metal comprises one or more of Ru, Pd, and Ir; In the XRD spectrum of the catalyst, the ratio of the normalized peak intensity per unit mass to the full width at half maximum (FWHM) of the characteristic peak of the active metal at 2θ of 39.5–43.0° is not greater than 1.5, and the ratio of the normalized peak intensity per unit mass to the full WHM of the characteristic peak at 2θ of 67.0–69.0° is not greater than 0.2.

[0037] The catalyst disclosed herein comprises a support and an active metal supported on the support; the support is a sulfur-modified carbon support, and the active metal includes one or more of Ru, Pd, and Ir; wherein, in the XRD pattern of the catalyst, the ratio of the normalized intensity of the metal per unit mass to the full width at half maximum (FWHM) of the characteristic peak at 2θ of 39.5–43.0° is not greater than 1.5, and the ratio of the normalized intensity of the metal per unit mass to the FWHM of the characteristic peak at 2θ of 67.0–69.0° is not greater than 0.2. Under high loading, the metal in the catalyst of this disclosure exists in the form of atomic clusters, exhibiting good dispersibility and higher activity and stability compared to commercial catalysts.

[0038] According to one embodiment of the present disclosure, in the XRD spectrum of the catalyst, the ratio of the normalized peak intensity per unit mass of the characteristic peak of the active metal at 2θ of 39.5~43.0° to the full width at half maximum (FWHM) is 0~1.5, and the ratio of the normalized peak intensity per unit mass of the characteristic peak at 2θ of 67.0~69.0° to the full width at half maximum (FWHM) is 0~0.2.

[0039] According to one embodiment of this disclosure, in the STEM image of the catalyst, the proportion of metal particles with regular lattice stripes is less than 60%, preferably 10-50%. The testing method of this disclosure involves randomly selecting a region under a STEM microscope, where the proportion of metal particles with regular lattice stripes to the total number of catalyst particles in that region is measured. In this disclosure, the active metal in the catalyst mostly exists in the form of atomic clusters, resulting in better dispersion and activity of the active metal.

[0040] According to one embodiment of this disclosure, based on the total mass of the catalyst, the mass fraction of the active metal is 1-70%, preferably 5-50%. In the above embodiment, under high loading, the active metal of the catalyst of this disclosure exists mostly in the form of atomic clusters, resulting in better dispersion and activity of the active metal.

[0041] According to one embodiment of this disclosure, the active metal is formed as atomic clusters, and the average particle size of the atomic clusters is 1-5 nm. This embodiment is beneficial for improving the activity of the catalyst.

[0042] According to one embodiment of this disclosure, the active metal is Ru, and the mass fraction of Ru, based on the total mass of the catalyst, is 1-70%, preferably 5-50%. In the XPS spectrum of the catalyst, the characteristic peak position of the 3p³ / ² peak of 0-valent Ru is 461.0-463.0 eV. In the XRD spectrum of the catalyst, a characteristic peak of Ru is present at 2θ of 41.5-43.0°. In this embodiment, compared with commercial ruthenium catalysts, the catalyst of this disclosure exhibits higher activity and stability because Ru exists in the form of atomic clusters under high loading.

[0043] According to one embodiment of this disclosure, the active metal is Ru. In the XRD pattern of the catalyst, no characteristic Ru peak is found at 2θ of 41.5–43.0°. Further X-ray absorption fine structure (XAFS) spectroscopy of the Ru K-edge under synchrotron radiation is used to determine the form of Ru. The coordination number of Ru-Ru bonds in conventional Ru nanocrystalline catalysts is 12. When the XAFS test results of the Ru K-edge show no Ru-Ru bonds or a Ru-Ru bond coordination number less than 12 for the Ru nanocrystalline catalyst, it can be determined that Ru exists in the form of atomic clusters. In this embodiment, compared to commercial ruthenium catalysts, the catalyst of this disclosure exhibits higher activity and stability as Ru exists in the form of atomic clusters under high loading.

[0044] According to one embodiment of this disclosure, the active metal is Ir, and the mass fraction of Ir is 1-70% based on the total mass of the catalyst; in the XPS spectrum of the catalyst, the characteristic peak position of the 4f 7 / 2 peak of 0-valent Ir is 60.8-61.4 eV; in the XRD spectrum of the catalyst, a characteristic peak of Ir exists at 2θ of 39.8-40.0°. In this embodiment, compared with commercial iridium catalysts, the catalyst of this disclosure exhibits higher activity and stability under high loading, with Ir existing in the form of atomic clusters.

[0045] According to one embodiment of this disclosure, the active metal is Ir. In the XRD pattern of the catalyst, no characteristic peak is found at 2θ of 39.8–40.0°. Further XAFS testing of Ir L3-edgeX using synchrotron radiation reveals that the Ir-Ir bond coordination number of conventional Ir nanocrystalline catalysts is 12. When the XAFS test result of Ir L3-edgeX shows no Ir-Ir bonds or an Ir-Ir bond coordination number less than 12 for Ir nanocrystalline catalysts, it indicates that Ir exists in the form of atomic clusters. In this embodiment, compared to commercial iridium catalysts, the catalyst of this disclosure exhibits higher activity and stability at high loadings, with Ir existing in the form of atomic clusters.

[0046] According to one embodiment of this disclosure, the active metal is Pd, and the mass fraction of Pd, based on the total mass of the catalyst, is 1-60%, preferably 5-50%. In the XPS spectrum of the catalyst, the characteristic peak position of the 3d 5 / 2 of 0-valent Pd is 335.2-335.5 eV, and the characteristic peak position of the 3d 5 / 2 of divalent Pd is 336.2-336.6 eV. In the XRD spectrum of the catalyst, a characteristic peak of Pd is present at 2θ of 39.0-40.0°. In this embodiment, compared with commercial palladium catalysts, the catalyst of this disclosure exhibits higher activity and stability at high loadings, with Pd existing in the form of atomic clusters.

[0047] According to one embodiment of this disclosure, the active metal is Pd. In the XRD pattern of the catalyst, no characteristic Pd peaks are found in the 2θ range of 39.0–40.0°. Further XAFS testing of the Pd K-edge using synchrotron radiation is performed. The coordination number of the Pd-Pd bond in conventional Pd nanocrystalline catalysts is 12. When the XAFS test result of the Pd K-edge shows no Pd-Pd bonds or a Pd-Pd bond coordination number less than 12 for Pd nanocrystalline catalysts, it indicates that Pd exists in the form of atomic clusters. In this embodiment, compared to commercial palladium catalysts, the catalyst of this disclosure exhibits higher activity and stability at high loadings, with Pd existing in the form of atomic clusters.

[0048] According to one embodiment of this disclosure, the total sulfur content in the sulfur-modified carbon support is 1-8% by weight, preferably 3-6% by weight; more preferably, the surface sulfur content of the sulfur-modified carbon support is 0.1-6% by weight, preferably 0.5-3% by weight. The above embodiment is beneficial for improving the dispersibility of the active component and further enhancing the activity of the catalyst.

[0049] A second aspect of this disclosure provides a method for preparing a metal cluster catalyst, the method comprising: (1) The metal source and the sulfur-modified carbon support are first impregnated in a solvent, and the precursor is obtained after removing the solvent; (2) The precursor is heat-treated at 230~480°C in an inert atmosphere; The metal source includes one or more of ruthenium, palladium, and iridium.

[0050] The method disclosed herein involves heat-treating a metal source and a sulfur-modified carbon support at a specific temperature under an inert atmosphere, which causes the active metal to form atomic clusters with better dispersion and higher activity.

[0051] According to one embodiment of this disclosure, in step (1), the method for preparing the sulfur-modified carbon support includes: subjecting the carbon support to a sulfur-containing solution for a second impregnation; the conditions for the second impregnation include: a temperature of 10-80°C, preferably 20-60°C, a time of 1-5 hours, preferably 2-4 hours, and a weight ratio of the carbon support to sulfur of 2-20:1, preferably 2-10:1. The above embodiment is beneficial for improving the dispersibility of the active component and further enhancing the activity of the catalyst.

[0052] According to one embodiment of this disclosure, the carbon carrier is conductive carbon black; preferably, the oxygen content of the conductive carbon black is 4% by weight or more, more preferably 5-10% by weight; the resistivity of the conductive carbon black is less than 10 Ω·m; and the specific surface area of ​​the conductive carbon black is 200-2000 m². 2 / g, preferably 800~1500m 2 / g. The above-described embodiments are beneficial for improving the dispersibility of the active components and further enhancing the activity of the catalyst.

[0053] According to one embodiment of this disclosure, the conductive carbon black includes one or more of EC-300J, EC-600JD, ECP600JD, VXC72, VXC72R, Black Pearls 2000, PRINTEX XE2-B, PRINTEX L6, and HIBLAXK 40B2.

[0054] According to one embodiment of this disclosure, the ruthenium source is a ruthenium-containing soluble compound, including one or more of ruthenium trichloride and ammonium ruthenate; in step (1), the amount of the ruthenium source, calculated as ruthenium element, is 0.01~2.4g relative to 1g of the sulfur-modified carbon support, preferably 0.1~1.5g. The above embodiment is advantageous because Ru exists in the form of atomic clusters at high loadings, resulting in better dispersion and improved catalyst activity.

[0055] According to one embodiment of this disclosure, the palladium source is a palladium-containing soluble compound, including one or more of palladium chloride, ammonium chloropalladate, and sodium chloropalladate; in step (1), the amount of the palladium source, calculated as palladium element, is 0.01~2.4g relative to 1g of the sulfur-modified carbon support, preferably 0.1~1.0g. The above embodiment facilitates the presence of Pd in ​​the form of atomic clusters at high loadings, resulting in better dispersion and improved catalyst activity.

[0056] According to one embodiment of this disclosure, the iridium source is an iridium-containing soluble compound, including one or more of chloroiridium acid and iridium trichloride; in step (1), the amount of the iridium source, calculated as iridium element, is 0.01~2.4g relative to 1g of the sulfur-modified carbon support, preferably 0.1~1.5g. The above embodiment is advantageous because Ir exists in the form of atomic clusters at high loadings, resulting in better dispersion and improved catalyst activity.

[0057] According to one embodiment of the present disclosure, in step (1), the conditions for the first impregnation include: the impregnation temperature is 10~40℃, preferably 20~35℃, and the impregnation time is 10h or more, preferably 15~24h.

[0058] According to one embodiment of this disclosure, in step (2), the inert atmosphere is one or more of nitrogen and argon; optionally, the heat treatment conditions include: a temperature of 240~400℃ and a time of 1~4h. The above embodiment facilitates the presence of active metals in the form of atomic clusters under high loading, resulting in better dispersion and improved catalyst activity.

[0059] The third aspect of this disclosure provides a metal cluster catalyst prepared by the method described in the second aspect of this disclosure.

[0060] This fourth aspect of the disclosure provides the application of the metal cluster catalysts described in the first and third aspects of the disclosure in water electrolysis and catalytic dehydrogenation reactions.

[0061] The present disclosure will be further described in detail below with reference to the embodiments. Unless otherwise specified, all reagents in this disclosure are commercially available.

[0062] Instruments, methods and conditions for XRD analysis: X-ray diffraction (XRD) analysis was performed on a Shimadzu XRD-6000 X-ray diffractometer from Japan. The test conditions included: tube voltage 40 kV, tube current 40 mA, Cu target Kα radiation, and 2θ scan range of 10° to 80°.

[0063] The X-ray photoelectron spectroscopy (XPS) analyzer was a VG Scientific ESCALab220i-XL model equipped with Avantage V5.926 software. The XPS analysis conditions were as follows: excitation source was monochromatic AlKα X-rays, power was 330 W, and the baseline vacuum was 3 × 10⁻⁶. -9 mbar. In addition, the electron binding energy was corrected using the C1s peak (284.3 eV) of elemental carbon, and the subsequent peaking software was XPSPEAK.

[0064] The total sulfur content was tested using a sulfur-carbon analyzer; the surface sulfur content was tested using an X-ray photoelectron spectroscopy analyzer.

[0065] The mass content of active metals was tested by ICP.

[0066] Aberration-corrected transmission electron microscopy (AC-STEM) was used, specifically the JEOL ARM200F model. The morphology and particle size of the metal particles were measured using STEM. The average particle size of the atomic cluster was calculated by taking 200 metal particles from the STEM image and calculating their average size.

[0067] X-ray absorption fine structure spectroscopy (XAFS) results were obtained using a synchrotron radiation source.

[0068] Ketjenblack ECP600JD (manufactured by Lion Corporation of Japan), with a specific surface area of ​​1362 m². 2 / g, pore volume 2.29mL / g, surface oxygen mass fraction 6.9wt%.

[0069] Commercial carbon-supported palladium catalyst (purchased from Damas-beta, brand name 80517D) with a metal loading of 10.0 wt%.

[0070] The following preparation examples are used to prepare sulfur-modified carbon supports.

[0071] Preparation Example 1 1.0 g of sulfur was dissolved in 70 ml of cyclohexane to form a homogeneous solution. 9.0 g of Ketjenblack ECP600JD was dispersed in the solution and stirred until homogeneous. The solution was then impregnated at 60 °C for 5 h and dried under vacuum at 50 °C to obtain sulfur-modified conductive carbon black.

[0072] The following examples are used to prepare catalysts.

[0073] Example 1 (1) Dissolve 0.4 g of palladium chloride (calculated as palladium) in a 0.1 M mixed solution. In the mixed solution, the volume ratio of dilute hydrochloric acid to ethanol is 10:1. Disperse 0.6 g of sulfur-modified conductive carbon black from Preparation Example 1 in the palladium chloride solution. Stir and disperse evenly. After impregnation and standing at 25 °C for 24 h, dry in a vacuum drying oven to obtain the precursor. The amount of palladium chloride used is 0.67 g relative to 1 g of sulfur-modified conductive carbon black (calculated as palladium). (2) The dried precursor was placed in a tube furnace and heated to 260°C at a rate of 5°C / min. After heat treatment and reduction in N2 atmosphere for 2 hours, the temperature was lowered to obtain 40% by mass of Pd / C catalyst.

[0074] The catalyst obtained in Example 1 was tested using XRD, XPS, XAFS, and STEM methods, as follows: Figures 1-2 and Figure 7 As shown in the XRD pattern of Example 1, a Pd characteristic peak exists at 39.5° 2θ. The ratio of the normalized intensity of the Pd characteristic peak per unit mass to the full width at half maximum (FWHM) is 1.44, and the ratio of the normalized intensity of the Pd characteristic peak per unit mass to the FWHM at 67.1° is 0.04. Combined with the XAFS results of Pd K-edge, the coordination number of the Pd-Pd bond is 5.5, indicating that the active metal Pd in ​​Example 1 exists in the form of atomic clusters. In the XPS pattern, the peak position of the 3d 5 / 2 characteristic peak of 0-valent Pd is 335.3 eV, and the peak position of the 3d 5 / 2 characteristic peak of divalent Pd is... The 5 / 2 characteristic peak is at 336.5 eV, shifted to a lower valence state by 0.4 eV; the XPS spectrum of S2p indicates the presence of S element in the support; further, the STEM image shows that the active component of the catalyst exists in the form of atomic clusters, and the proportion of metal particles with regular lattice stripes is 24.1%, with an average particle size of 3.1 nm.

[0075] Example 2 The method in this embodiment is the same as that in Example 1, except that ruthenium trichloride is used instead of palladium chloride to obtain a Ru / C catalyst with a loading of 40% by mass.

[0076] The catalyst obtained in Example 2 was tested using XRD, XPS, XAFS, and STEM methods, such as... Figure 3 , Figure 5 and Figure 8As shown in the XRD pattern of Example 2, a Ru characteristic peak exists at 2θ of 42.7°. The ratio of the normalized peak intensity per unit mass of the Ru characteristic peak to the full width at half maximum (FWHM) is 0.90. Furthermore, at 68.0°, the ratio of the normalized peak intensity per unit mass of the Ru characteristic peak to FWHM is 0.17. Combined with the XAFS results of the Ru K-edge, the coordination number of the Ru-Ru bond is 3.8, indicating that the active metal Ru in Example 2 exists in the form of atomic clusters. In the XPS pattern, the 3p 3 / 2 characteristic peak of 0-valence Ru is at 462.0 eV, shifting 0.4 eV towards a higher valence state. The S2p XPS pattern indicates the presence of S element in the support. Further analysis of the STEM image shows that the active component of the catalyst exists in the form of atomic clusters, with metal particles exhibiting regular lattice fringes accounting for 25.0% of the total, and the average particle size of the atomic clusters being 2.7 nm.

[0077] Example 3 The method in this embodiment is the same as that in Example 1, except that chloroiridic acid is used instead of palladium chloride to obtain an Ir / C catalyst with a loading of 40% by mass.

[0078] The catalyst obtained in Example 3 was tested using XRD, XPS, XAFS, and STEM methods, such as... Figure 4 , Figure 6 and Figure 9 As shown in the XRD pattern of Example 3, an Ir characteristic peak exists at 2θ of 40.0°. The ratio of the normalized peak intensity per unit mass to the full width at half maximum (FWHM) of the Ir characteristic peak is 1.0, and the ratio of the normalized peak intensity per unit mass to FWHM of the characteristic peak at 68.3° is 0.2. Combined with the XAFS results of Ir L3-edge, the coordination number of the Ir-Ir bond is 4.2, indicating that the active metal Ir in Example 3 exists in the form of atomic clusters. In the XPS pattern, the peak position of the 4f 7 / 2 characteristic peak of 0-valence Ir is 61.2 eV, shifted to a higher valence state by 0.6 eV. The S2p XPS pattern indicates the presence of S element in the support. Furthermore, the STEM image shows that the active component of the catalyst exists in the form of atomic clusters, and the proportion of metal particles with regular lattice fringes is 14.5%, with an average particle size of 1.9 nm.

[0079] Example 4 The method in this embodiment is the same as that in Example 1, except that: the amount of palladium chloride used is 0.1g and the amount of sulfur-modified conductive carbon used is 0.9g, so as to obtain a Pd / C catalyst with a loading of 10% by mass.

[0080] The catalyst obtained in Example 4 was tested using XRD, XPS, XAFS, and STEM methods, as follows: Figures 1-2 and Figure 10As shown in the XRD pattern of Example 4, there are no Pd characteristic peaks in the 2θ range of 39–43°, and the ratio of the normalized peak intensity to the full width at half maximum (FWHM) is 0. Similarly, there are no Pd characteristic peaks in the 2θ range of 67–69°, and the ratio of the normalized peak intensity to FWHM is 0. Combined with the XAFS results of the Pd K-edge, the coordination number of the Pd-Pd bond is 2.0, indicating that the active component Pd in ​​Example 4 exists in the form of atomic clusters. In the XPS pattern, the peak position of the 3d⁵ / ² characteristic peak of 0-valent Pd is 335.4 eV, and the peak position of the 3d⁵ / ² characteristic peak of 2-valent Pd is 336.4 eV, shifting 0.5 eV towards lower valence states. The S²p XPS pattern indicates the presence of S element in the support. Further analysis of the STEM image shows that the active component of the catalyst exists in the form of atomic clusters, and the proportion of metal particles with regular lattice fringes is 0%, with an average particle size of 1.6 nm for the Pd metal atomic clusters.

[0081] Example 5 The method in this embodiment is the same as that in embodiment 1, except that in step (2), the heat treatment temperature is 470°C.

[0082] The XRD and XPS spectra of the catalyst in Example 5 were the same as those in Example 1. Pd in ​​the catalyst existed in the form of atomic clusters, and the proportion of metal particles with regular lattice stripes was 38.4%, with an average particle size of 3.6 nm.

[0083] Example 6 The method in this embodiment is the same as that in Example 1, except that: the amount of palladium chloride used is 0.6g and the amount of sulfur-modified conductive carbon used is 0.4g, so as to obtain a Pd / C catalyst with a loading of 60% by mass.

[0084] The XRD and XPS spectra of the catalyst in Example 6 were the same as those in Example 1. Pd in ​​the catalyst existed in the form of atomic clusters, and the proportion of metal particles with regular lattice stripes was 54.8%, with an average particle size of 4.5 nm.

[0085] Comparative Example 1 The commercial palladium catalyst was purchased as 10% by mass of a commercial palladium catalyst, brand name 80517D.

[0086] XRD and XPS tests were performed on the catalyst of Example 1, and the results are as follows: Figures 1-2As shown, a Pd characteristic peak exists at 2θ of 40.1°, and the ratio of the normalized peak intensity per unit mass to the full width at half maximum (FWHM) of the Pd characteristic peak is 3.1. Furthermore, the ratio of the normalized peak intensity per unit mass to FWHM of the characteristic peak at 68.2° is 0.17, indicating that the active metal Pd in ​​Comparative Example 1 mainly exists in the form of nanocrystals. In the XPS spectra, the peak position of the 3d⁵ / ² characteristic peak of 0-valent Pd is 335.2 eV, and the peak position of the 3d⁵ / ² characteristic peak of divalent Pd is 336.9 eV. The proportion of metal particles with regular lattice fringes is 51%, and the average particle size of metallic Pd is 5.2 nm.

[0087] Comparative Example 2 The method in this embodiment is the same as that in embodiment 1, except that in step (2), the heat treatment atmosphere is N2:H2 with a volume ratio of 4:1 and the heat treatment temperature is 150°C.

[0088] The catalyst in Example 2 was tested using XRD and XPS, such as... Figures 1-2 As shown in the XRD pattern of Comparative Example 2, a Pd characteristic peak exists at 2θ of 39.8°. The ratio of the normalized peak intensity per unit mass to the full width at half maximum (FWHM) of the Pd characteristic peak is 4.7, and the ratio of the normalized peak intensity per unit mass to the FWHM of the characteristic peak at 68.1° is 3.3, indicating that the active metal Pd in ​​Comparative Example 2 mainly exists in the form of nanocrystals. In the XPS pattern, the peak position of the 3d 5 / 2 characteristic peak of 0-valent Pd is 335.4 eV, and the peak position of the 3d 5 / 2 characteristic peak of divalent Pd is 336.6 eV. The proportion of metal particles with regular lattice fringes is 58.6%, and the average particle size of Pd particles is 3.3 nm.

[0089] Comparative Example 3 The method used in this comparative example is the same as that in Example 1, except that the carrier used is unmodified conductive carbon black Ketjenblack ECP600JD.

[0090] The XRD and XPS spectra of the catalyst in Comparative Example 3 are similar to those in Comparative Example 2; the STEM images are as follows. Figure 11 As shown, the active component of the catalyst in Comparative Example 3 mainly exists in the form of nanocrystals, and the proportion of metal particles with regular lattice stripes is 62.3%, with an average particle size of 3.6 nm for Pd particles.

[0091] Test Example 1 The performance of the catalysts prepared in Examples 1, 4-6, and Comparative Examples 1-3 in catalytic hydrogenation reactions was determined. The test method included: nitrobenzene and the catalyst were loaded into a high-pressure reactor lined with PTFE at a nitrobenzene:Pd molar ratio of 30000:1, and the reactor was purged with H2. The reactor temperature was heated to 70°C and maintained, while the hydrogen pressure was kept at 0.4 MPa. After reacting for 2 hours, the reactor was placed in cold water to terminate the reaction. After separating the solid catalyst, the liquid product and unconverted reactants were analyzed by gas chromatography-mass spectrometry (GC-MS).

[0092] The stability test method includes: after the reaction is completed, the catalyst is filtered out, washed with deionized water and dried, and the reaction in Example 1 is repeated, and the yield of aniline in the 5th reaction is recorded.

[0093] The test results are shown in Table 1.

[0094] Table 1

[0095] As can be seen from the data in Table 1, compared with Comparative Example 1, the catalyst disclosed herein, at the same loading, has active components existing in the form of atomic clusters, exhibiting higher activity and stability.

[0096] Compared to Comparative Example 2, the catalyst prepared under specific conditions according to this disclosure exhibits higher activity and stability.

[0097] Compared to Comparative Example 3, the use of sulfur-modified carbon support in this disclosure can improve the dispersibility of active metals, resulting in higher catalyst activity and stability.

[0098] Comparing Examples 1 and 5, it is evident that the catalyst exhibits higher activity within the preferred heat treatment conditions of this disclosure. Comparing Examples 1 and 6, it is evident that the catalyst exhibits higher activity within the preferred dosage range of the active metal of this disclosure.

[0099] Test Example 2 The alkaline HER performance of the catalyst in Example 2 was measured, and the results are shown in Table 2.

[0100] The catalyst is prepared into a uniformly dispersed slurry and coated onto a glassy carbon electrode with a diameter of 5 mm. The amount of metal catalyst on the electrode is controlled within the range of 8-10 μg. iR correction is required during calculation.

[0101] The test method for hydrogen evolution reaction (HER) of water electrolysis includes: the polarization curve LSV of the catalyst is tested at 2500 rpm in 1.0 M KOH saturated with N2, with a potential range of -0.2~0.2 V (vs. RHE) and a scan rate of 0.01 V / s.

[0102] Table 2

[0103] In commercial Ru black catalysts, Ru exists in the form of nanocrystals, with an active component content of 100%. The amount of active metal on the electrode is 86 μg, and under the same test conditions as this application, the overpotential is 125 mV. As shown in Table 2, compared to commercial Ru black catalysts, the catalyst disclosed in this application exhibits a lower overpotential, higher activity, and better stability with a smaller amount of Ru.

[0104] Test Example 3 The alkaline OER performance of the catalyst in Example 3 was measured, and the results are shown in Table 3.

[0105] The catalyst was prepared into a uniformly dispersed slurry and coated onto a glassy carbon electrode with a diameter of 5 mm. The amount of metal catalyst on the electrode was controlled to be 40 μg. iR correction was required for the calculation.

[0106] The test method for the oxygen evolution reaction (OER) of water electrolysis includes: the polarization curve LSV of the catalyst is tested at 2500 rpm in 0.5 M H2SO4 saturated with N2, with a potential range of 1.36~1.56 V (vs. RHE) and a scan rate of 0.01 V / s.

[0107] Table 3

[0108] In the commercially available pure Ir black catalyst (purchased from Shanghai Hesen), the active component is formed as atomic clusters with an average particle size >4 nm. The content of the active component is 99.99 wt%, and the amount of active metal on the electrode is 300 μg. Under the same test conditions as this application, the overpotential is 262 mV. As shown in Table 3, compared to the commercially available pure Ir black catalyst, the catalyst disclosed in this application exhibits a lower overpotential, higher activity, and better stability with a smaller dosage.

[0109] The preferred embodiments of this disclosure have been described in detail above with reference to the accompanying drawings. However, this disclosure is not limited to the specific details of the above embodiments. Within the scope of the technical concept of this disclosure, various simple modifications can be made to the technical solutions of this disclosure, and these simple modifications all fall within the protection scope of this disclosure.

[0110] It should also be noted that the various specific technical features described in the above embodiments can be combined in any suitable manner without contradiction. To avoid unnecessary repetition, this disclosure will not describe the various possible combinations separately.

[0111] Furthermore, various different embodiments of this disclosure can be combined in any way, as long as they do not violate the spirit of this disclosure, they should also be regarded as the content disclosed in this disclosure.

Claims

1. A metal cluster catalyst, characterized in that, The catalyst comprises a support and an active metal supported on the support; the support is a sulfur-modified carbon support, and the active metal comprises one or more of Ru, Pd, and Ir; In the XRD spectrum of the catalyst, the ratio of the normalized peak intensity per unit mass to the full width at half maximum (FWHM) of the characteristic peak of the active metal at 2θ of 39.5–43.0° is not greater than 1.5, and the ratio of the normalized peak intensity per unit mass to the full WHM of the characteristic peak of the metal at 2θ of 67.0–69.0° is not greater than 0.

2.

2. The catalyst according to claim 1, wherein, In the STEM image of the catalyst, the proportion of metal particles with regular lattice stripes is less than 60%, preferably 10-50%.

3. The catalyst according to claim 1, wherein, Based on the total mass of the catalyst, the mass fraction of the active metal is 1-70%, preferably 5-50%.

4. The catalyst according to claim 1, wherein, The active metal is formed into atomic clusters, and the average particle size of the atomic clusters is 1~5nm.

5. The catalyst according to claim 1, wherein, The active metal is Ru, and the mass fraction of Ru is 1-70% based on the total mass of the catalyst. In the XPS spectrum of the catalyst, the 3p 3 / 2 characteristic peak of 0-valent Ru is located at 461.0~463.0 eV; In the XRD pattern of the catalyst, a Ru characteristic peak is present or absent at 2θ of 39.5~43.0°.

6. The catalyst according to claim 1, wherein, The active metal is Ir, and the mass fraction of Ir is 1-70% based on the total mass of the catalyst. In the XPS spectrum of the catalyst, the characteristic peak position of 4f 7 / 2 for 0-valent Ir is 60.8~61.4 eV; In the XRD pattern of the catalyst, there is an Ir characteristic peak or no Ir characteristic peak at 2θ of 39.5~43.0°.

7. The catalyst according to claim 1, wherein, The active metal is Pd, and the mass fraction of Pd is 1-60%, preferably 5-50%, based on the total mass of the catalyst. In the XPS spectrum of the catalyst, the peak position of the 3d 5 / 2 characteristic peak of 0-valent Pd is 335.2~335.5 eV, and the peak position of the 3d 5 / 2 characteristic peak of divalent Pd is 336.2~336.6 eV; In the XRD pattern of the catalyst, a Pd characteristic peak is present or absent at 2θ of 39.5~43.0°.

8. The catalyst according to claim 1, wherein, In the sulfur-modified carbon support, the total sulfur content is 1-8% by weight, preferably 3-6% by weight. Preferably, the sulfur content on the surface of the sulfur-modified carbon support is 0.1-6% by weight, and more preferably 0.5-3% by weight.

9. A method for preparing a metal cluster catalyst, characterized in that, The method includes: (1) The metal source and the sulfur-modified carbon support are first impregnated in a solvent, and the precursor is obtained after removing the solvent; (2) The precursor is heat-treated at 230~480°C in an inert atmosphere; The metal source includes one or more of ruthenium, palladium, and iridium.

10. The method according to claim 9, wherein, In step (1), the method for preparing the sulfur-modified carbon support includes: subjecting the carbon support to a second impregnation with a solution containing sulfur; The conditions for the second impregnation include: a temperature of 10~80℃, a time of 1~5h, and a weight ratio of the carbon carrier to sulfur of 2~20:

1.

11. The method according to claim 9, wherein, The carbon carrier is conductive carbon black; the oxygen content of the conductive carbon black is 4% by weight or more; the resistivity of the conductive carbon black is less than 10 Ω·m; and the specific surface area of ​​the conductive carbon black is 200~2000 m². 2 / g.

12. The method according to claim 9, wherein, The ruthenium source is a ruthenium-containing soluble compound, including one or more of ruthenium trichloride and ammonium ruthenate. In step (1), the amount of ruthenium source, calculated as ruthenium, is 0.01~2.4g relative to 1g of the sulfur-modified carbon support, preferably 0.1~1.5g.

13. The method according to claim 9, wherein, The palladium source is a palladium-containing soluble compound, including one or more of palladium chloride, ammonium chloropalladate, and sodium chloropalladate; In step (1), the amount of palladium source, calculated as palladium element, is 0.01~1.5g relative to 1g of the sulfur-modified carbon support, preferably 0.1~1.0g.

14. The method according to claim 9, wherein, The iridium source is an iridium-containing soluble compound, including one or more of chloroiridium acid and iridium trichloride; In step (1), the amount of the iridium source, calculated as iridium, is 0.01 to 2.4 g, preferably 0.1 to 1.5 g, relative to 1 g of the sulfur-modified carbon support.

15. The method according to claim 9, wherein, In step (1), the conditions for the first impregnation include: the impregnation temperature is 10~50℃, preferably 15~40℃, and the impregnation time is more than 10h, preferably 15~24h.

16. The method according to claim 9, wherein, In step (2), the inert atmosphere is one or more of nitrogen and argon; Optionally, the heat treatment conditions include: a temperature of 240~400℃ and a time of 1~4h.

17. A metal cluster catalyst prepared by the method according to any one of claims 9 to 16.

18. The use of the catalyst according to any one of claims 1 to 8 and 17 in water electrolysis and catalytic addition / dehydrogenation reactions.